Analytical assessment of heterocyclic compound degrading ability of biphenyl derading marine bacteria - Nurul Farahidayu, Binti ab Hadi (Universiti Malaysia Sarawak (UNIMAS), 2012)
Biphenyl is a kind of a heterocyclic compound with some toxicity and may form during incomplete combustion of mineral oil and coal and may cause toxic thus pollute the environment. Due to this, bioremediation is the way to reduce the pollutant that caused by the biphenyl into the environment by introducing biphenyl-degrading marine bacteria (Asturias & Timmis, 1993). Analytical assessment of heterocyclic compound degrading ability of biphenyl degrading marine bacteria is to identify the degradation rate of biphenyl. In this study, a method that was used to identify the ability and examined the degradation rate of marine bacteria isolate for biphenyl degradation is to precultivated isolate and inoculated the culture for 14 days. Then the culture was analyzed by using analytical method such as GCIFID. Chromohalobacter marismortui which is biphenyl-degrading bacteria showed a concentration-dependent growth in all concentration of biphenyl they grew in and were visible changes color of the growth medium of the isolates during their incubation, suggesting the production of different substrates.